Partisipasi politik Masyarakat Nelayan Sungai Limau Dalam Pemilu Legislatif Tahun 1999 - Budi Juliardi (Bakaba, 2018)
This research aims to see the level of political participation of fishing communities in the District of Sungai Limau in the 1999 legislative elections, namely in Jorong Pasir Baru and Sungai Sirah. This goal is achieved through a qualitative approach by following the steps that are applied Milles and Huberman. Informants determined by using the snow ball sampling techniques that include fishing (fishing boat owners and fishermen, workers), wife of fishermen, wali jorong, as well as public figures. The study findings suggest that the level of political participation of fishing communities in the legislative elections Sungai Limau  in 1999 are higher when compared with the level of political participation at before election period, namely 96.2% in Sungai Sirah and 94.12% in Pasir Baru or above 90% . Sungai Limau fishing communities take advantage of the freedom of choice provided by Era Reformasi to choose according to their wishes.